Strengthening Intergovernmental Cooperation to Eradicate Extreme Poverty in Indonesia - Andari , Soetji (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
According to the Central Statistics Agency, the number of people living in extreme poverty in Indonesia stood at 2.2 million (0.78%) in September 2025. In 2024, through integrated policy interventions across government sectors, the government aims to eliminate extreme poverty. This study aims to analyze how collaborative governance among the government, non-governmental organizations, and the community contributes to addressing extreme poverty. The research method employed a descriptive qualitative approach. Data collection was conducted through in-depth interviews, document analysis, and field observations to understand policy processes, actor interactions, and local perceptions of poverty alleviation programs. The research findings indicate that collaborative governance enhances policy effectiveness by mobilizing institutional capacity and community resources. Three main approaches were identified, namely: Social support as a tool for social protection; community empowerment to enhance economic capacity and develop basic infrastructure such as clean water, electricity, transportation, and digital connectivity. This study emphasizes that collaboration among various stakeholders and integrated policy planning are essential for achieving sustainable reductions in extreme poverty at the local level.